New Model Armies: Rethinking Military Purpose in Post-Conflict Southeastern Europe - Marley, Jonathan (Journal of Regional Security, 2018)
New and novel military structures have emerged across the region in the context of externally driven post-conflict defence reform. As the post-conflict narrative gives way to new domestic, regional and international challenges and opportunities, elements of the process remain unresolved. This paper will argue that in order to establish a sustainable and efficient military platform three emerging and interrelated lacunae need to be addressed: knowledge deficits in civilian-military relations; ownership cleavages as a result of adherence to Euro- Atlantic integration; and legitimacy of military function beyond the post-conflict context.